2017
DOI: 10.1001/jamainternmed.2017.5824
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hospital Resource Use and Outcomes Among Hospitalists, Primary Care Physicians, and Other Generalists

Abstract: IMPORTANCE A physician's prior experience caring for a patient may be associated with patient outcomes and care patterns during and after hospitalization.OBJECTIVE To examine differences in the use of health care resources and outcomes among hospitalized patients cared for by hospitalists, their own primary care physicians (PCPs), or other generalists. DESIGN, SETTING, AND PARTICIPANTSThis retrospective study analyzed admissions for the 20 most common medical diagnoses among elderly fee-for-service Medicare pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 26 publications
2
83
0
Order By: Relevance
“…Hospitalists currently deliver inpatient care in around 75 percent of hospitals in the United States . However, since hospitalists, as an internal medicine specialty, have not been around for a long time, questions about the value added by hospitalists remain . Our findings support previous studies that found a positive relationship between hospitalists and lower readmission rates, resource use, and length of stay .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Hospitalists currently deliver inpatient care in around 75 percent of hospitals in the United States . However, since hospitalists, as an internal medicine specialty, have not been around for a long time, questions about the value added by hospitalists remain . Our findings support previous studies that found a positive relationship between hospitalists and lower readmission rates, resource use, and length of stay .…”
Section: Discussionsupporting
confidence: 84%
“…However, since hospitalists, as an internal medicine specialty, have not been around for a long time, questions about the value added by hospitalists remain . Our findings support previous studies that found a positive relationship between hospitalists and lower readmission rates, resource use, and length of stay . Employment ensures hospitalists' commitment to the organization and allows hospitalists to attain leadership roles in the hospital.…”
Section: Discussionsupporting
confidence: 81%
“…Any individual resident bias in performing POCUS examinations was mitigated by the large variety of patient presentations and substantial number of residents sampled in this study, which represents one of the largest single‐center experiences of its kind. Although it was anticipated that residents would preferably perform CLUE on patients with cardiopulmonary conditions or more ill noncardiac presentations, it is noteworthy that 33% of CLUE US applications lacked all of the cardiopulmonary signs; that 35% of patients had been discharged within 2 days; and that the average length of stay for this acutely admitted study population, 5.6 ± 8.1 days, was similar to the 5‐day rate reported in national databases of total admissions. It is unlikely that consecutive sampling of all admissions would have changed the study's findings, and it would have made the data less applicable to practice in different hospitals.…”
Section: Discussionmentioning
confidence: 56%
“…However, more recent data suggest that fewer primary care physicians follow their patients across settings. For example, a patient's primary care physician was the hospital attending in only 14.2 percent of admissions by Medicare beneficiaries in 2013 …”
Section: Discussionmentioning
confidence: 99%